Biological Activity and Nanostructuration of Fe3O4-Ag/High Density Polyethylene Nanocomposites - Phuong Nguyen-Tri (Journal of Composites Science, 2019)
We report here the synthesis of uniform nanospheres-like silver nanoparticles (Ag NPs, 5–10 nm) and the dumbbell-like Fe3O4-Ag hybrid nanoparticles (FeAg NPs, 8–16 nm) by the use of a seeding growth method in the presence of oleic acid (OA)/oleylamine (OLA) as surfactants. The antibacterial activity of pure nanoparticles and nanocomposites by monitoring the bacterial lag–log growth has been investigated. The electron transfer from Ag NPs to Fe3O4 NPs which enhances the biological of silver nanoparticles has been proven by nanoscale Raman spectroscopy. The lamellae structure in the spherulite of FeAg NPs/High Density Polyethylene (HDPE) nanocomposites seems to play the key role in the antibacterial activity of nanocomposites, which has been proven by nanoscale AFM-IR. An atomic force microscopy coupled with nanoscale infrared microscopy (AFM-IR) is used to highlight the distribution of nanoparticles on the surface of nanocomposite at the nanoscale. The presence of FeAg NPs in PE nanocomposites has a better antibacterial activity than that reinforced by Ag NPs due to the faster Ag+ release rate from the Fe3O4-Ag hybrid nanoparticles and the ionization of Ag NPs in hybrid nanostructure.